Perbaikan Tanah Lempung Ekspansif Menggunakan Soda Api (NaOH) - Bambang Pardoyo; Sri Prabandiyani Retno Wardani; Windu Partono (Diponegoro University, 2018)
An expansive clay is soil material that is composed of various minerals include kaolinite, montmorillonite and illite group. Mineral montmorilinite have the sensitivity to the effects of the water is very easy to swell and shrink. High and low levels of swelling and shrinkage (shrinkage) expansive clay is determined by the high and low content of montmorillonite on expansive clay granules. Because of these properties are very high content of montmorillonite often cause problems in the building. This study uses a solution of Soda Api (NaOH) as a stabilizer through the compaction process Modified Proctor on (OMC + 7,5%) Proctor standard by the number of collisions each - each is 10 x, 25x and 56x, and the amount of additional water on weight soil dry , with variations in increments of water by 95% : 5% NaOH, water by 90%: 10% NaOH and water by 85% : 15% NaOH. This research was conducted testing - testing in the laboratory include: Index properties, Swelling Pressure, Swelling Potential and CBR with curing and no curing. Results - results in these tests show that the value of the property index showed an increase, Test UCS showed an decrease, Test CBR by soaking at the age of 7 days with a mixture of caustic soda 10% showed the best results, while the pressure test expands and Test Potential expands decreased significant.